2013
DOI: 10.1001/jamaoto.2013.5217
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Section Pathology for Decision Making in Parotid Surgery

Abstract: Frozen section pathology for parotid lesions has high accuracy and utility in intraoperative decision making, facilitating timely complete procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 5 publications
0
51
0
Order By: Relevance
“…Knowing the presence of positive superficial intraparotid nodes is critical information to determine the need for a deep lobe parotidectomy. When the pathologist can tell if a primary parotid tumor is a high-grade carcinoma and reports the status of the superficial nodes, operative decision making can proceed regarding performing a neck dissection and deep lobe removal [27].…”
Section: Pathologymentioning
confidence: 99%
“…Knowing the presence of positive superficial intraparotid nodes is critical information to determine the need for a deep lobe parotidectomy. When the pathologist can tell if a primary parotid tumor is a high-grade carcinoma and reports the status of the superficial nodes, operative decision making can proceed regarding performing a neck dissection and deep lobe removal [27].…”
Section: Pathologymentioning
confidence: 99%
“…Every effort should be made to preserve facial nerve when it is not directly invaded by tumor; however, the surgeon should be prepared to perform a total parotidectomy that may y extend into the temporal bone to allow for a proximal negative margin resection of the facial nerve if involved. Intraoperative frozen section helps de ine histology and guides surgical execution [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Frozen section maybe useful in 3 scenarios : (1) confirmation/clarification of preoperative diagnosis, (2) assessment of surgical margins, and (3) determine whether nerve or neck involvement is present. Intraoperative frozen section has been shown to be useful in distinguishing benign from malignant [28, 29], however this may not add much when deciding how to manage FN involvement, extending the operation to address the deep lobe or cervical lymph nodes or terminating surgery in the case of lymphoma. Olson et al reported on use of intraoperative frozen section in stratifying lymphoma or carcinoma, low-grade or high-grade malignant tumor, status of the intraparotid nodes in a high volume setting.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%